The excitation of OH by H2 revisited – II. Hyperfine resolved rate coefficients. Issue 3 (24th February 2020) - Kłos, J; Dagdigian, P J; Alexander, M H; Faure, A; Lique, F
ABSTRACT: Observations of hyperfine resolved transitions of the hydroxyl radical (OH) are unique probes of the physical conditions in molecular clouds. In particular, hyperfine intensities can be used as an effective thermometer over a wide range of molecular densities. Accurate modelling of the OH emission spectra requires the calculation of collisional rate coefficients for the excitation of OH by H2, the most abundant collisional partner in the molecular clouds. Here, we determine hyperfine resolved rate coefficients for the excitation of OH by H2 using a recently developed highly accurate potential energy surface. State-to-state rate coefficients between the lower hyperfine levels were calculated using recoupling techniques for temperature ranging from 10 to 150 K. Significant differences were found with the earlier values currently used in astrophysical models, the new rate coefficients being larger than the previous ones. Finally, we compute the excitation of the OH radical in cold molecular clouds and star-forming regions. The new rate coefficients were found to increase the hyperfine intensities by a factor of ∼1–2. Consequently, we recommend using this new set of data in any astrophysical model of OH excitation.